Oxotris(oxalato)niobate(V) as counterion in cobalt(II) spin-crossover systems. (15th October 2016) - Oliveira, Willian X.C.; Pereira, Cynthia L.M.; Pinheiro, Carlos B.; Krambrock, Klaus; Grancha, Thais; Moliner, Nícolas; Lloret, Francesc; Julve, Miguel
Graphical abstract: The six-coordinate cobalt(II) complex of formula [Co(terpy)2 ]3 [NbO(C2 O4 )3 ]2 ·3CH​3 OH·3H2 O shows a thermally induced spin-crossover behavior from a high-spin state (HS, S = 3/2) at higher temperatures to a low-spin phase (LS, S = 1/2) at lower temperatures, the LS configuration being achieved at T ⩽ 200 K. Abstract: This work is devoted to the investigation of the thermally induced spin-crossover behavior from a high-spin state (HS, S = 3/2) at higher temperatures to a low-spin phase (LS, S = 1/2) at lower temperatures of the six-coordinate cobalt(II) complex in the compound [Co(terpy)2 ]3 [NbO(C2 O4 )3 ]2 ·3CH​3 OH·4H2 O (2 ). The crystal structure of2 together with that of its counterion as tetraphenylarsonium(V) salt (AsPh4 )3 [NbO(C2 O4 )3 ]·9H2 O (1 ) are also included. The spin-crossover process was followed by the thermal variation of the χ M T product between 2.0 and 400 K under the warming mode, with the LS configuration being achieved at T ⩽ 200 K and the LS → HS interconversion being incomplete at 400 K. X-band EPR measurements both in solution and in the solid state were used to characterize the LS state. In order to substantiate the phenomenon in2, an analytical expression was presented based on the combination of the spin–orbit coupling and both first- and second-order Zeeman effects for a d 7 electronic configuration. The best-fit parameters were C vib = 0.0249, λ = −163 cm −1, α = 1.06, Δ = 1532 cm −1, with a fixed value of g LS = 2.11 determined from the fit of the EPR spectrum at 10 K.